La cooperación interparlamentaria e intergubernamental de las comunidades autónomas en asuntos europeos tras la STC 31/2010 - Fernández Alles, José Joaquín (Revista de Derecho Político, 2010)
En los últimos cuatro años, el sistema político español ha adquirido una nueva configuración jurídica como consecuencia de las reformas estatutarias del periodo 2006-2010 y del Tratado de Lisboa de 13 diciembre de 2007, en vigor desde el 1 de diciembre de 2009. Junto a la participación autonómica en el proceso decisorio europeo, en el ámbito parlamentario, el Tratado de Lisboa y dos de sus Protocolos han justificado, asimismo, la aprobación de la Ley 24/2009, de 22 de diciembre, de modificación de la Ley 8/1994, de 19 de mayo, por la que se regula la Comisión Mixta para la Unión Europea, y el derecho de los Parlamentos a participar en el procedimiento de control de la subsidiariedad. Se trata, además, de tres conjuntos normativos que abren un nuevo campo de estudio a la relación entre poderes y, conforme a una interpretación sistemática y un entendimiento integrador del Estado, permiten fundamentar y ampliar las competencias y funciones parlamentarias al proceso decisorio europeo, a la cooperación descentralizada y a las relaciones interparlamentarias. Conforme a este planteamiento, y a la luz de la doctrina del Tribunal Constitucional (STC 31/2010, de 28 de junio), en este trabajo analizamos tres aspectos fundamentales de las competencias y funciones europeas del sistema parlamentario español: a) La configuración legal de estas competencias y funciones; b) La participación orgánica de las Comunidades Autónomas en las fases ascendente y descendente del proceso decisorio europeo; y c) Las funciones de los Parlamentos autonómicos en sistema de alerta temprana para el control de los principios de subsidiariedad y proporcionalidad. During the last four years, the Spanish politic system parliamentary ha acquired a new configuration as a result of the reforms of the Statutes of autonomies (2006-2010) and the Treaty of Lisbon of 13 December 2007, that entered into force on 1 December 2009. Furthermore, the Treaty of Lisbon and two of its Protocols have justified also the adoption of Law 24/2009, of December 22, which amends the Law 8/1994, of May 19, regulating the Joint Congress-Senate Committee for EU matters, and the right of the Autonomous Parliament to participate in the monitoring principles of subsidiarity and proportionality. This body of rules has opened a new field of study on the relationship between powers and, according to a systematic and inclusive understanding of the State, can increase autonomic functions to the participation in the European decision-making, the decentralized cooperation and cross-border and to interparliamentary relations. In this paper we analyze three key aspects of european competences and functions of the Autonomous Comunities, following the doctrine of the Constitutional Court (STC 31/2010, of 28 June): a) The configuration of these parliamentary competences and duties; b) The organic participation of the Autonomous Communities in the European decision-making, and c) The functions of th spanish parliamentary system in the early warning system for monitoring the principles of subsidiarity and proportionality in accordance with the Organic Law 1/2008, of July 30, which authorizes the ratification by Spain of the Treaty of Lisbon, and the Law 24/2009, of December 22, which amends the Law 8/1994, of May 19, regulating the Joint Congress- Senate Committee for EU matters. We propose an integrative and conceptual reconstruction of the parliamentary law, oriented to be a relational order of different legislative powers: the State, the European Union and the Autonomous Communities.